2021
DOI: 10.1021/acs.jpcb.1c02962
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water Extraction on Malonamide Aggregation: A Molecular Dynamics and Graph Theoretic Approach

Abstract: Solution structure in liquid−liquid extraction affects the efficacy of separation; however, even for simplified organic phases, structural characterization and attribution of aggregation to intermolecular interactions are fundamental challenges. We investigate water uptake into organic phases for two malonamides commonly applied to actinide and lanthanide separations. Extracted water induces reorganization of the amphiphilic extractant molecules, although we find this rearrangement is not strongly manifested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Extractant aggregation is quantified by using both geometric and thermodynamic descriptions. For the geometric description, a graph-theoretic cluster analysis is performed on the extractant molecules 59,61,100 using the position of the carbon connecting the two amide groups and a distance cutoff of 10 Å, taken from the first minimum in the radial distribution function (RDF) for pairs of that atom type (see Fig. 11).…”
Section: Resultsmentioning
confidence: 99%
“…Extractant aggregation is quantified by using both geometric and thermodynamic descriptions. For the geometric description, a graph-theoretic cluster analysis is performed on the extractant molecules 59,61,100 using the position of the carbon connecting the two amide groups and a distance cutoff of 10 Å, taken from the first minimum in the radial distribution function (RDF) for pairs of that atom type (see Fig. 11).…”
Section: Resultsmentioning
confidence: 99%
“…Our aim in this article is to study the metal-free i-SANEX system, exploring the link between molecular interactions and the aggregates that result. Previous simulations of metal-free systems have shown that diglycolamides form reverse structures in a non-polar diluent, and there has been extensive analysis of the molecular organization of these clusters and the distributions of cluster sizes and compositions. ,, A very recent article reports the results of large-scale simulations of the TODGA/ n -dodecane/water/nitric acid system as well as providing a detailed description of the molecular structure of the aggregates …”
Section: Introductionmentioning
confidence: 99%
“…The overall size of the aggregates increases for the acid-equilibrated L I /L II system because of the accumulation of HNO 3 and H 2 O in the aggregate core. The co-extraction of acid and water along with the metal ions are well reported for different ligands used in the NFC. ,, ,, The aggregation of the ligand in the nonpolar medium is mainly driven by the extraction of acid, metal ions, sand water in the organic phase. ,, ,,, For example, the selectivity of the trivalent metal ion by TODGA is driven by the spherical aggregate formation by the extraction of the acid and water in the organic phase . We have also determined the uptake of water and acid by the L I /L II dissolved in the 20% isodecanol +80% n -dodecane at 3 M HNO 3 (for experimental details, see ESI).…”
Section: Resultsmentioning
confidence: 80%
“…12,13,15−18,36,70−72 The aggregation of the ligand in the nonpolar medium is mainly driven by the extraction of acid, metal ions, sand water in the organic phase. 11,12,[14][15][16][17]36,70,71 For example, the selectivity of the trivalent metal ion by TODGA is driven by the spherical aggregate formation by the extraction of the acid and water in the organic phase. 9 We have also determined the uptake of water and acid by the L I /L II dissolved in the 20% isodecanol +80% ndodecane at 3 M HNO 3 (for experimental details, see ESI).…”
Section: ■ Results and Discussionmentioning
confidence: 99%